Yield and Quality of Kenaf Seed as Influenced by De-Topping and Spacing Under Transplanting Method - Mollah, A.F.; Rahman, M. M.; Tareq, M. Z.; Hasan, M.M.; Hoque, A.B.M.Z. (International Journal of Applied Sciences and Biotechnology, 2015)
An experiment was conducted at the Bangladesh Jute Research Institute (BJRI), Regional Station, Kishoreganj, Bangladesh during July to December 2010 and 2011 to study the effect of spacing and time of de-topping on yield and quality of kenaf seed cv. HC-95 grown under transplanting method. The experiment comprised three plant spacing (viz., 40 cm × 15 cm, 30 cm × 15 cm and 20 cm × 15 cm) and five de-topping (viz., no de-topping, de-topping at transplanting, de-topping at 15, 30 and 45 days after transplanting (DAT) in a Randomized Complete Block Design (RCBD) with three replications. The highest yield of kenaf seed was obtained from planting at 30 cm × 15 cm spacing. The best quality seed in respect to germination and vigour was also obtained from transplanting at 30 cm × 15 cm spacing. The highest seed yield, germination and vigour of seed were obtained for de-topped at 30 DAT. The study concludes that late season kenaf produces highest seed yield with best quality when planted at 30 cm x 15 cm spacing and for de-topping at 30 DAT. Int J Appl Sci Biotechnol, Vol 3(4): 626-634